Effects of different blood-pressure-lowering regimens on major cardiovascular events: results of prospectively-designed overviews of randomised trials. - Turnbull, F (2003)
BACKGROUND: The benefits of reducing blood pressure on the risks of major cardiovascular disease are well established, but uncertainty remains about the comparative effects of different blood-pressure-lowering regimens. We aimed to estimate effects of strategies based on different drug classes (angiotensin-converting-enzyme [ACE] inhibitors, calcium antagonists, angiotensin-receptor blockers [ARBs], and diuretics or beta blockers) or those targeting different blood pressure goals, on the risks of major cardiovascular events and death. METHODS: We did seven sets of prospectively-designed overviews with data from 29 randomised trials (n=162341). The trial eligibility criteria, primary outcomes, and main hypotheses were specified before the result of any contributing trial was known. FINDINGS: In placebo-controlled trials the relative risks of total major cardiovascular events were reduced by regimens based on ACE inhibitors (22%; 95% CI 17-27) or calcium antagonists (18%; 5-29). Greater risk reductions were produced by regimens that targeted lower blood pressure goals (15%; 5-24). ARB-based regimens reduced the risks of total major cardiovascular events (10%; 4-17) compared with control regimens. There were no significant differences in total major cardiovascular events between regimens based on ACE inhibitors, calcium antagonists, or diuretics or beta blockers, although ACE-inhibitor-based regimens reduced blood pressure less. There was evidence of some differences between active regimens in their effects on cause-specific outcomes. For every outcome other than heart failure, the difference between randomised groups in achieved blood pressure reduction was directly related to the observed difference in risk. INTERPRETATION: Treatment with any commonly-used regimen reduces the risk of total major cardiovascular events, and larger reductions in blood pressure produce larger reductions in risk.